PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT IBU DAN ANAK HARAPAN BUNDA PRINGSEWU LAMPUNG: PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI RUMAH SAKIT IBU DAN ANAK HARAPAN BUNDA PRINGSEWU LAMPUNG - Fahlefi, Wilis; Yuliantoharinugroho, Yuliantoharinugroho; Rofik, Mochamad (PRIMA EKONOMIKA, 2023)
The purpose of this study was to determine the influence of work discipline and work environment on employee performance at the Harapan Mother and Child Hospital, Bunda Pringsewu Lampung. The population in this study was all employees of the Mother's Hospital and Mother's Hope Bunda Pringsewu Lampung, while the sample used a saturated sample where the entire population of 67 people was used as a sample. Data collection was carried out by distributing questionnaires to respondents. Collection technique using SPSS.17. Data analysis uses multiple regression. Based on the results of the study, it was stated that work discipline and work environment have an effect and significant effect on the performance of employees of the Harapan Mother and Child Hospital Bunda Pringsewu Lampung. Keywords : Discipline, Environment and Performance.